Nilai-Nilai Pendidikan Agama Islam pada Anak Usia Dini - Istiqlaliyah, Hulailah (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2023)
Learning needs that are increasingly complex cause a decrease in learning, especially those related to Islamic religious values in early childhood. The formation of Islamic religious values in early childhood is a very important foundation laying the foundation of religion so that a person can obey religion. The purpose of this research is to analyze the importance of Islam in early childhood. The research method of this research uses a literature search through data collection of scientific articles and previous research. The results of the research show that Islamic religious values can be taught through exemplary habits and actions. As a teacher and parent, you must try to have a good personality in order to be an example for children. Teachers and parents must always increase their knowledge, understanding and skills related to the development of Islamic religious values in early childhood.